2019
DOI: 10.1109/jiot.2019.2940251
|View full text |Cite
|
Sign up to set email alerts
|

Optimization-Oriented RAW Modeling of IEEE 802.11ah Heterogeneous Networks

Abstract: The new medium access method of IEEE 802.11ah, called Restricted Access Window (RAW), divides stations into different groups, and only allows stations in the same group to access the channel simultaneously, in order to reduce collisions and thus achieve better performance (e.g., throughput). However, the existing station grouping strategies only support homogeneous scenarios where all stations use the same modulation and coding scheme (MCS) and packet size. A surrogate model is an efficient mathematical model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 29 publications
0
8
0
1
Order By: Relevance
“…This observation is reflected in a recent survey on 802.11ah research [318] where, out of about 200 cited references, only three consider multi-hop scenarios. Moreover, surprisingly, only two papers by Tian et al [319], [320] deal with applying ML: both use a form of SL to optimize the parameters of 802.11ah's grouping functionality, restricted access window (RAW). A similar problem is also addressed by Mahesh and Harigovindan [321], where an MLP NN configures these parameters considering, i.a., network size and MCS values used.…”
Section: Sensor Networkmentioning
confidence: 99%
“…This observation is reflected in a recent survey on 802.11ah research [318] where, out of about 200 cited references, only three consider multi-hop scenarios. Moreover, surprisingly, only two papers by Tian et al [319], [320] deal with applying ML: both use a form of SL to optimize the parameters of 802.11ah's grouping functionality, restricted access window (RAW). A similar problem is also addressed by Mahesh and Harigovindan [321], where an MLP NN configures these parameters considering, i.a., network size and MCS values used.…”
Section: Sensor Networkmentioning
confidence: 99%
“…Related studies concerning RAW optimization are presented here, and details are shown in Table 5 . The current solutions for RAW optimization in the literature primarily focus on enhancing the network performance in terms of throughput [ 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 115 ], channel efficiency/utilization [ 97 , 104 , 116 , 117 , 118 ], and energy consumption [ 59 , 102 , 105 , 111 , 112 , 119 , 120 , 121 , 122 , 123 , 124 ].…”
Section: Mac Features Of the Ieee 80211ah And Current Resource Alloca...mentioning
confidence: 99%
“…Normal data is divided into non-regular data that is transmitted at a certain amount of data, depending on the nature of the signal, and regular data that the data transmission time is fixed according to the time limit. Redundant data reduces the efficiency of the network at the time of transmission, thereby reducing network efficiency overall [17]. It is removed immediately if duplicate data is found using the cosine duplication function, and it also improves transmission efficiency by eliminating redundant data in the incoming data.…”
Section: E Proposed Mac Protocol 1) Eliminate Redundant Data With Cos...mentioning
confidence: 99%